How did problem-based learning with the TPACK approach (PBL-TPACK) enhance physics learning outcomes? - Daimul Hasanah; Yuli Prihatni; Lisdayanti Lisdayanti; Joko Purwanto (Universitas Ahmad Dahlan, 2023)
This study aimed to determine the average score category of students' physics learning outcomes and the effect of the PBL-TPACK on students' physics learning outcomes. This research is a type of quantitative research with a comparative approach. The research design used was a randomized pretest-posttest design. The sample was randomly selected, and two class groups were chosen as the research sample. The data collection technique was carried out using a test technique. The data collection instrument was a test instrument with multiple choice questions of 30 test items with five alternative answers. The results showed that the average score of students' physics learning outcomes taught by the PBL-TPACK was included in the high category. In contrast, the DI-TPACK was included in the low sort, and there is a significant difference in average physics learning outcomes between students taught through the PBL-TPACK and those taught through the DI-TPACK. The PBL-TPACK has a positive effect on students' physics learning outcomes.